2020
DOI: 10.3961/jpmph.20.159
|View full text |Cite
|
Sign up to set email alerts
|

Age-period-cohort Analysis of Healthy Lifestyle Behaviors Using the National Health and Nutrition Survey in Japan

Abstract: Objectives: This study conducted an age-period-cohort (APC) analysis of trends in healthy lifestyle behaviors in Japan. Methods: We used National Health and Nutrition Survey data on salt intake and prevalence of smoking, drinking, and physical activity between 1995 and 2018 in Japan. Age groups were defined from 20 to 69 years old in 10-year increments. Cohorts were defined for each age group of each year with a 1-year shift, and cohorts born in 1926-1935 (first cohort) until 1989-1998 (last cohort) were exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
(25 reference statements)
1
8
1
Order By: Relevance
“…The prevalence of heavy and moderate alcohol drinking largely varied depending on age, particularly in men. The prevalence tended to increase with age for men and decrease from the middle ages for women according to a previous study on the prevalence of alcohol drinking in Japan [2]. This is consistent with the results of the current study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The prevalence of heavy and moderate alcohol drinking largely varied depending on age, particularly in men. The prevalence tended to increase with age for men and decrease from the middle ages for women according to a previous study on the prevalence of alcohol drinking in Japan [2]. This is consistent with the results of the current study.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the results of the current study. In addition, drinking prevalence was shown to decrease over the birth cohorts, particularly in men [2]. The increase of the prevalence of moderate drinking with age is considered to reflect the decrease of the prevalence over the cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a previous study showed that the relationship between areal SES and mortality varied depending on sex for some cancer types [ 8 ]. In addition, trends in the prevalence of certain health behaviors differs depending on sex in the analyzed periods in Japan [ 12 ], and it is possible that the trends in the relationship between SES and mortality would also vary depending on sex for some diseases. Therefore, this study also focused on sex differences in the relationship between SES and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 However, the smoking prevalence was shown to increase in cohorts of men born between the 1930s and 1970s and in women born between the 1940s and 1970s. 25 Therefore, other factors are considered to be related to the cohort effect on dyslipidemia prevalence among women.…”
Section: Discussionmentioning
confidence: 99%